Detection of Human Breathing Using Signal Processing Techniques Under Debris - Erenoglu, Mehmet Z.; Aldirmaz-Colak, Sultan; Tokan, Nurhan Turker (IEEE, 2024)
It is of paramount importance to rescue a human trapped in a collapsed building quickly and effectively. In such search and rescue operations, radar technology is an effective tool used to detect living humans beneath the debris. In this work, we have applied time-frequency domain techniques; namely, Short-Time Fourier Transform (STFT), Wavelet Transform (WT) to the radar signal for detecting the movement of conscious or unconscious human beings that are trapped in a building debris. To mitigate noise effect on the measured signal, denoising techniques are performed. The performance of the methods is experimentally verified by using the debris model that was created in the laboratory. The signal processing techniques provide critical information and enable rapid detection of the human trapped under the debris.
Keywords: Breathing detection; Fourier transform; Remote sensing; SFCW; STFT; WT; Computer Science